Wealth protection in the context of maqasid syariah: Malaysia’s role in realizing the concept of economic jihad - Mohamad Sabri Haron, (Penerbit Universiti Kebangsaan Malaysia, 2017)
In maqasid syariah (objectives of syariah) of wealth is an important wasilah (tool) in achieving the highest objective in of Islam, i.e., the protection of the Islamic faith. Hence, Malaysia regards economic activities as important jihad in order to achieve human wellbeing. Malaysia has introduced the Islamic Banking Act 1983 which produces Bank Islam Malaysia Berhad. At the same time, conventional banking system in Malaysia has also opened a ‘window’ for Islamic banking system to operationalize in their respective banks which is at present widely expanded under the supervision of Bank Negara Malaysia. This paper attempts to explain the concept of Islamic wealth protection in the context of maqasid syariah, and discusses Malaysia‘s role in applying Islamic wealth protection according to maqasid syariah in its Muslim community, in particular, through potential Islamic finance institutions in Malaysia using economic jihad approach.